A DOUBLE FUNCTION EQUIPMENT OF A DRYER CONCURRENTLY A WATER DISTILLER BY SOLAR AND WIND ENERGIES FOR THE DEVELOPMENT OF COASTAL AREAS - Diyono . (JOURNAL OF COASTAL DEVELOPMENT, 2000)
The aim of the study is to create double-function equipment comprises the use of a dryer in the rainy seasons and of water distillation in dry seasons. The main components consists of a windmill as the sources of mechanical power to move the blower or water dipper and a drying room doubling as a distilling room by solar energy.